A Critical Node: The Role of China in the Transnational Circulation of Developmentalist Ideas, Policies and Practices. Issue 6 (2nd November 2022) - Eaton, Sarah; Katada, Saori N.
ABSTRACT: How do developmentalist ideas emerge, and how are they transmitted and adopted? This special section explores the transnational circulation of developmentalist ideas, policies, and practices through mainland China. Taking the International Relations diffusion paradigm as our starting point, we critically engage with common conceptions of diffusion as a one-way process either within the Global North or from Global North to South. We call for both taking multidirectional flows of ideas and norms seriously and also attending to agency exercised both on the supplying and demanding sides of diffusion processes. By setting our sights on diffusion dynamics to and from a powerful non-Western state (China), our project joins recent research illuminating the role of nation-states beyond the trans-Atlantic domain as active agents and participants, rather than passive recipients, in the creation of global economic norms, policies and practices.